The Dynamics of Foreign Direct Investment in Sub-Saharan Africa : Challenges and Opportunities - Alvaro Javier Forteza; Maximo Rossi; Marcel Vaillant (International Forum of Researchers and Lecturers, 2024)
Foreign Direct Investment (FDI) is a key driver of economic growth in many developing regions, but its effectiveness in Sub-Saharan Africa has been mixed. This paper examines the dynamics of FDI in the region, exploring both the challenges and opportunities it presents for economic development. The research identifies factors such as political instability, infrastructure deficits, and regulatory barriers that hinder FDI inflows, as well as the potential benefits such as technology transfer, employment, and market expansion. It concludes with policy recommendations aimed at improving the FDI climate in Sub-Saharan Africa.